Efficient Construction by Implementation of Lean Management Principles - Chandrakar, Vinay Kumar Singh; Jain, Ankur Dev (International Journal of Scientific Research in Civil Engineering, 2019)
This dissertation work was carried out on implementation of lean management principles in the construction industry with the focus on reducing wastes generated during the construction process and to increase the efficiency of resource utilization. Construction industry is one of the most unorganized, and complicated sectors. Also, this sector is financially dominated by use of material resources and workforce which makes it a highly complex and expensive sector. After identifying the issues concerning with this industry, the new technique is applied for increasing the efficiency and reducing the time consumption associated with this field. So, to achieve this goal, a method has been researched until that concept came which was already implemented successfully in the manufacturing sector. Then after brainstorming, that concept had been applied in construction industry which showed the potential of streamlining and the work processes. This leads to increase the output with comprehensive resource usage in the least possible time. In order to implement lean in construction, use the methodology of Value Stream Mapping because while doing this research work, we realized that this method unlike others, Essential features of lean construction includes a clear set of objects at project level. Lean construction helped us to practically visualize current state of the project and identify the wastes, which made it aqua clear to prepare a future state map with the evaluated results. In general lean construction project are easier to manage, safer, completed sooner, &less cost with better quality
Keywords: Lean; Construction; Management & Implementation